2018
DOI: 10.1007/s10903-018-0801-y
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Accidents Among Nepali Male Workers in the Middle East and Malaysia: A Qualitative Study

Abstract: There are many Nepali men working in the Middle East and Malaysia and media reports and anecdotal evidence suggest a high risk of workplace-related accidents and injuries for male Nepali workers. Therefore, this study aims to explore the personal experiences of male Nepali migrants of unintentional injuries at their place of work. In-depth, face-to-face interviews (n = 20) were conducted with male Nepali migrant workers. Study participants were approached at Kathmandu International Airport, hotels and lodges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Many studies have been carried out of injuries in those who have moved to another country to work, as permanent residents, seasonal contracted employees or as legal or undocumented immigrants, most (for example) but not all find immigrant workers to be at greater risk of workplace injury. Studies not finding an excess have largely been those comparing migrant and local workers in the same work or migrants who have come to skilled jobs or have been settled in the host country over many years .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out of injuries in those who have moved to another country to work, as permanent residents, seasonal contracted employees or as legal or undocumented immigrants, most (for example) but not all find immigrant workers to be at greater risk of workplace injury. Studies not finding an excess have largely been those comparing migrant and local workers in the same work or migrants who have come to skilled jobs or have been settled in the host country over many years .…”
Section: Introductionmentioning
confidence: 99%
“… 5 16 17 19 21–24 26–34 41 Only two studies were qualitative in nature. 36 38 Nine studies focused specifically on Nepalese migrants as their primary study population 5 7 32–38 while the remaining 24 studies mentioned Nepalese migrant workers as part of a sub-analysis ( table 1 ). In majority of the studies, there was a lack of disaggregated data on demographic characteristics of Nepalese migrant workers.…”
Section: Resultsmentioning
confidence: 99%
“…25 One qualitative study explored workplace accidents in GCC and Malaysia and reported several issues faced by the workers including lack of workplace safety, long working hours resulting in dehydration, heat stroke, injuries and accidents-related issues including life-long disability. 36 …”
Section: Resultsmentioning
confidence: 99%
“…After securing written informed consent, a topic guide was used as a prompt for questioning. The fi rst author conducted the face-toface in-depth interviews using a semi-structured guide in venues suitable for the participants 10 . The guide was developed in English and translated into Nepali for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to fatalities due to extreme working conditions, naivety to safety at work and individual behaviours, many Nepalese migrant workers also experienced mental health problems and problems including stress, loneliness, hopelessness and frustration in the Middle East and Malaysia [8][9][10] . This qualitative study explores the role of social support and support networks among Nepali migrant workers in the Middle East and Malaysia.…”
Section: Introductionmentioning
confidence: 99%